Establishing Literacy Foundations : Policies and Interventions for Indonesia's Future Excellence - Riki Nasrullah; Kisyani Laksono; Arditya Prayogi; Parmin Parmin; Fafi Inayatillah (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study explores the current condition of children's literacy in Indonesia focusing on several critical issues including the impact of inequality in literacy access, the factors influencing the quality of teaching languages, exploring the development of local literacy cultures and reading preferences in order to create a more inclusive literacy program, and the evaluation of current literacy policies. A policy analysis and document/library analysis method with qualitative research approach were used to gather data from documentation studies of literacy policies, reports on implementation and current literatures related to children's literacy in Indonesia. The data analysis technique of this research applied thematic analysis to review, identify, and analyze the data. The results showed that Indonesia still experiences a protracted learning crisis, particularly in relation to children's literacy. Factors like low literacy activities, Covid-19 pandemic and the results of national assessments indicate a serious challenge regarding the performance of children's literacy. Limited children's reading interest and availability of suitable book collections also pose a challenge to overcome. The study proposes several steps to improve children's literacy in Indonesia, including increasing accessibility and variety of book collections, enhancing collaboration between relevant authorities, harmonising with the global literacy standards, widening access to books, particularly in rural communities, involving the local community and establishing corporate partnerships with private sectors. The study hopefully provides a meaningful contribution to developing solutions to Indonesia's children's literacy challenges and strategies to improve children's literacy.